2020
DOI: 10.1021/acs.jafc.0c03735
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Indole Pyruvate Pathway for Tryptophan Metabolism Mediated by IL4I1

Abstract: L-tryptophan (Trp) is widely used in food and feed enforcement to play an important role in biological processes. Various metabolites of Trp perform its potent function. The indole pyruvate pathway is one of the main pathways of Trp metabolism in the gut microbiota, providing numerous indole-derivatives, which can modulate intestinal homeostasis and mucosal immunity by activating the aryl hydrocarbon receptor (AHR) signaling pathway. In this study, we constructed an IL4I1-overexpressed 293T cell line and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…Aryl-pyr-As are the intermediate metabolites of aryl-LAs [13]. Aryl-pyr-As have been reported as endogenous metabolite mediators in the host, such as AhR ligands [26,27]. Using our assay system, we confirmed the ligand activity of IpyA against AhR (Figure 3H).…”
Section: Ahr Ligand Activity Of Aryl-lassupporting
confidence: 61%
“…Aryl-pyr-As are the intermediate metabolites of aryl-LAs [13]. Aryl-pyr-As have been reported as endogenous metabolite mediators in the host, such as AhR ligands [26,27]. Using our assay system, we confirmed the ligand activity of IpyA against AhR (Figure 3H).…”
Section: Ahr Ligand Activity Of Aryl-lassupporting
confidence: 61%
“…This effect appears to involve diminution of mTORC1 signaling (Cousin et al, 2015). However, it has also been recently observed that IL4I1 degradation of tryptophan [a minor substrate in comparison to phenylalanine (Boulland et al, 2007)] produces indole derivatives that can activate the AHR pathway (Sadik et al, 2020;Zhang et al, 2020). Finally, IL4I1 modulates the priming of CD8 + T cells.…”
Section: Consequences Of Amino-acid Catabolizing Enzyme Activity On Tmentioning
confidence: 99%
“…Fortunately, microbiota-mediated Trp metabolites serve as a reliable source of AhR ligands and influence the activity of AhR. Some intestinal symbiotic bacteria can metabolize Trp and produce numerous metabolites, such as indole, tryptamine, and indole derivatives IAAId, IAA, IAId, and IPA, which have been proved to exhibit species selective preference upon combining with AhR and firmly elucidate the activation of AhR, [74,78,79,95] and thus are involved in regulating immune response and affecting intestinal function. For example, IAId with AhR activation release IL-22 that could guarantee mucosal defense mechanisms and intestinal homeostasis.…”
Section: Intestinal Microorganism-mediated Indole Pathwaymentioning
confidence: 99%